Inflation and Money Demand in Albania - Kalra, Sanja (IMF Working Papers; Working Paper ;, 1998)
The paper uses a simple analytical framework to estimate relationships between prices, money the exchange rate, and interest rates in Albania during 1993-97. The estimated parsimonious error correction model extends the findings of a growing literature on inflation and money demand in transition economies. The results suggest that, after the one-time effects of the 1997 crisis are taken into account, the long-run determinants of inflation and money demand remained unchanged. Strong financial policies since mid-1997 appear to have helped to restore conditions for low inflation and stable money demand.